2019
DOI: 10.3389/fneur.2019.00560
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Disease and Perioperative Neurologic Vulnerability: A Prospective Cohort Study

Abstract: Background: Stroke is a devastating perioperative complication without effective methods for prevention or diagnosis. The objective of this study was to analyze evidence-based strategies for detecting cerebrovascular vulnerability and injury in a high-risk cohort of non-cardiac surgery patients. Methods: This was a single-center, prospective cohort study. Fifty patients undergoing non-cardiac surgery were recruited −25 with known cerebrovascular disease and 25 matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 44 publications
(61 reference statements)
1
15
0
Order By: Relevance
“…A recent prospective cohort study of noncardiac surgery patients revealed that modified National Institutes of Health (Bethesda, Maryland) stroke scale changes were common postoperatively. 71 Increased scores, compared with preoperative baseline, were found in 20% of low-risk patients and more than 30% of high-risk patients. Such tools may thus have a low positive predictive value in the immediate postoperative setting.…”
Section: Screening and Diagnostic Considerationsmentioning
confidence: 93%
See 2 more Smart Citations
“…A recent prospective cohort study of noncardiac surgery patients revealed that modified National Institutes of Health (Bethesda, Maryland) stroke scale changes were common postoperatively. 71 Increased scores, compared with preoperative baseline, were found in 20% of low-risk patients and more than 30% of high-risk patients. Such tools may thus have a low positive predictive value in the immediate postoperative setting.…”
Section: Screening and Diagnostic Considerationsmentioning
confidence: 93%
“…However, currently, there are no clinically validated, reliable biomarkers for detecting cerebral ischemia and infarction. 71 Thus, currently available clinical screening tools and serum biomarkers are not presently recommended for routine postoperative screening. A targeted examination that focuses on signs and symptoms of large-vessel occlusion (table 3) may improve stroke detection.…”
Section: Screening and Diagnostic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute value of rSO 2 is difficult to interpret without context. Indeed, we have reported catastrophic ischemic neurological injury without noteworthy perturbation in cerebral oximetry values [15] and, despite meta-analysis, the effect of perioperative NIRS monitoring of the brain remains uncertain [16]. Trend monitoring has been previously suggested as the most appropriate application for cerebral oximetry [3]; our data support no more than this use.…”
Section: Discussionmentioning
confidence: 63%
“…That animal model corroborates the present findings and suggests that haemodiluting Hb below 7‐8 g/dL is too large to maintain cerebral oxygenation although increased arterio‐venous O 2 ‐extraction may secure cerebral oxygen consumption. Carotid atherosclerosis is seen in 20%‐30% of vascular surgical patients 1,4 and may reduce brain perfusion pressure, the capacity to increase oxygen extraction, and impair cerebral autoregulation 24 . Cerebral perfusion is sensitive to changes in MAP 25 but MAP was identical in the two groups.…”
Section: Discussionmentioning
confidence: 99%